Should conditions regarding non-discrimination be imposed in vertical mergers? The surface transportation board on the acquisition of the Kansas City Southern Railway by the Canadian Pacific - Russell W. Pittman (U.S. Department of Justice, Antitrust Division, Expert Analysis Group (EAG), 2024)
In its 2023 decision approving the acquisition of the Kansas City Southern Railway by the Canadian Pacific, the U.S. Surface Transportation Board conditioned its approval on the merged railway's commitment "to keep gateways open on commercially reasonable terms" - that is, to allow shippers and non-merging railroads to continue to enjoy the option of using joint-line service, despite the merger's creation of the alternative of single-line service on the merged railroad. A century has passed since the Board's predecessor agency, the Interstate Commerce Commission, first imposed a condition of the maintenance of open gateways as a condition for approving a rail merger. This paper asks three questions. First, exactly what, in practice, are open gateways? Second, how have the two regulatory agencies dealt with the inherent tension between maintaining open gateways and achieving merger efficiencies? Third, what is the current state of play?
Keywords: 330; Russell Pittman; ATR; DOJ; The Surface Transportation Board; Kansas City Southern Railway; Canadian Pacific